39 Long-term outcomes of a randomized comparison of drug-eluting stents versus bare metal stents in saphenous vein graft lesions – 5-year follow-up of the isar-cabg trial. (5th October 2017) - Colleran, R; Kufner, S; Mehilli, J; Rosenbeiger, C; Schupke, S; Hoppmann, P; Fusaro, M; Abdel-Wahab, M; Neumann, FJ; Richardt, G; Ibrahim, T; Schunkert, H; et al.
Abstract : Background: In the ISAR-CABG (Is Drug-Eluting Stenting Associated with Improved Results in Coronary Artery Bypass Grafts?) trial, clinical outcomes at 1 year were superior in patients randomized to treatment of saphenous vein graft lesions (SVG) with drug-eluting stents (DES) compared with bare metal stents. The aim of this analysis was to compare clinical outcomes between treatment groups at 5-year follow-up. Methods: Patients with symptoms or objective evidence of myocardial ischaemia in the presence of >50% de novo stenosis of saphenous vein grafts undergoing PCI were randomly allocated (1:1) to treatment with DES or bare metal stents. Within the DES group, patients were randomized (1:1:1 allocation) to treatment with one of 3 drug-eluting stent types: early generation paclitaxel-eluting stent or sirolimus-eluting stent or new generation biodegradable polymer sirolimus-eluting stent. The primary endpoint was the combined incidence of death, myocardial infarction, or target lesion revascularization (TLR). Secondary endpoints were the combined incidence of death or myocardial infarction, TLR and definite stent thrombosis. Results: 610 patients were randomized to treatment with DES (n=303) or BMS (n=307). There were no differences in baseline clinical, lesion or procedural characteristics between treatment groups. At 5 years, the primary endpoint occurred in 159 (55·5%) patients in the DES group vs. 157 (53·6%) patients in the bare metal stent group (hazard ratio [HR] HR 0·98, 95% CI 0·79–1·23, P=0·89): death or myocardial infarction in 93 (32·8%) versus 108 (36·6%) patients (HR 0·85, 95% CI 0·64–1·12, P=0·24) and target lesion revascularization in 84 (33·1%) vs. 69 (25.5%) patients (HR 1·20, 95% CI 0·87–1·64, P=0·27) (Figure, Panel A), respectively. The incidence of definite stent thrombosis was in 5 (2·0%) vs. 1 (0·4%) patients in the DES and bare metal stent groups, respectively (5·11 (0·60–44·72), p=0.14). There was an interaction between the treatment effect with time for both the primary endpoint and TLR (Pinteraction =0·004 and <0.001, respectively). Landmark analysis showed that despite significantly lower rates of the primary endpoint and TLR in the DES group compared with the bare metal stent group at one year, between 1 and 5 years, the primary endpoint occurred numerically more frequently in the DES group (HR 1·28, 95% CI 0·97–1·68, P=0·08), driven by a significantly higher rate of TLR (HR 2·07, 95% CI 1·36–3·16, P=0·001) (Figure, Panel B). There was no significant difference in incidence of any endpoint among the 3 groups randomized to treatment with the 3 DES types studied. Conclusion: In patients undergoing treatment of SVG lesions, the clinical advantage of DES over bare metal stents demonstrated at 1 year was not sustained at 5-year follow-up due to higher attrition of efficacy in the DES group.